Fluorine-free binder of silk fibroin cross-linked polyacrylic acid as well as preparation method and application of fluoride-free binder
By using a fluorine-free binder of crosslinked polyacrylic acid with silk fibroin, the problem that traditional binders cannot adapt to the volume expansion of silicon negative electrodes is solved, and the stability of the electrode structure and the electrochemical performance of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202510055500.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
Traditional binders cannot adapt to the phenomenon of large volume expansion of silicon negative electrodes during circulation, resulting in electrode powdering and falling off, affecting the electrochemical performance of lithium-ion batteries.
A fluorine-free binder with cross-linked polyacrylic acid in silk fibroin is used to construct a bond network structure with enhanced cohesion and enhance the structural stability of the electrode through the hydrogen bond interaction between silk fibroin and polyacrylic acid.
It effectively alleviates the problem of electrode structure rupture, improves the electrochemical performance and cycle stability of lithium-ion batteries, and fully utilizes the characteristics of high capacity of silicon negative electrodes.
Smart Images

Figure CN119852407A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a fluorine-free binder of silk fibroin cross-linked polyacrylic acid, and a preparation method and application thereof. Background Art
[0002] The graphite anode material currently used is close to 372 mAh g -1 The specific capacity of 5G high-power electronic products is far from meeting the demand for high-performance lithium-ion batteries. Silicon negative electrode materials have a theoretical specific capacity that is more than 10 times that of graphite negative electrode materials, and have become the most promising alternative material to meet this demand. However, when silicon is used as a negative electrode material in lithium-ion batteries, it still faces problems such as significant volume expansion changes (>300%) during the cycle, resulting in structural fragmentation, pulverization, poor long-cycle stability, and poor conductivity that limits ion diffusion, which limits the excellent performance of lithium-ion batteries. The use of traditional binders cannot solve the above-mentioned problem of large volume expansion, and it is difficult to give full play to the advantages of the high capacity of silicon negative electrode materials.
[0003] Binders are important components of electrodes, mainly adhering active materials and conductive carbon black to current collectors. The forces between them generally include van der Waals forces, hydrogen bonds, electrostatic interactions and covalent bonds. Silk fibroin can transform from conformation I (amorphous and α-helical structure) to conformation II (β-folded structure) under different external environmental conditions (such as pH value, temperature and solvent type). The formation of β-folded structure significantly improves cohesion due to the increase in its internal hydrogen bond density and the strengthening of intermolecular interactions. How to reasonably utilize silk fibroin to prepare a binder with good adhesion and cohesion is crucial to improving and enhancing the electrochemical performance of batteries and is the focus of current research. Summary of the invention
[0004] The purpose of the present invention is to address the deficiencies in the prior art, such as the inability of traditional binders to adapt to the large volume expansion of silicon negative electrodes during cycling, which leads to powdering and shedding of the electrodes and causes poor electrochemical performance of the battery. A binder with enhanced cohesion is provided to alleviate phenomena such as electrode structure rupture, thereby improving the electrochemical performance of the battery.
[0005] To achieve the above object, the present invention provides a fluorine-free binder of silk fibroin cross-linked polyacrylic acid, which comprises the following steps:
[0006] S1. dissolving polyacrylic acid in deionized water to prepare a polyacrylic acid colloidal solution with a mass fraction of 3-10%;
[0007] S2, dissolving silk fibroin in deionized water to prepare a silk fibroin solution with a mass fraction of 3-10%;
[0008] S3, mixing the polyacrylic acid colloidal solution of step S1 and the silk fibroin solution of step S2 uniformly according to the ratio of silk fibroin to the total mass of polyacrylic acid and silk fibroin to obtain a mixed colloidal solution;
[0009] S4, adding ethanol solution to the mixed colloidal solution of step S3 to transform the disordered silk fibroin into an ordered state, and then heating and drying to obtain a fluorine-free binder of silk fibroin cross-linked polyacrylic acid.
[0010] As a further preferred technical solution of the present invention, the resistivity of the deionized water is 18.2 MΩ.m.
[0011] As a further preferred technical solution of the present invention, the mass fraction of the ethanol solution is 1-5%.
[0012] As a further preferred technical solution of the present invention, the temperature of the heating and drying is 100-150°C.
[0013] As a further preferred technical solution of the present invention, in step S3, the mixture is stirred and mixed for at least 30 minutes.
[0014] As a further preferred technical solution of the present invention, the molecular weight (Mn) of the polyacrylic acid is 420-460 kDa, and the molecular weight (Mn) of the silk fibroin is 6-10 kDa.
[0015] As a further preferred technical solution of the present invention, in step S3, the silk fibroin accounts for 20-40% of the total mass of the polyacrylic acid and the silk fibroin.
[0016] According to another aspect of the present invention, the present invention further provides a fluorine-free binder, which is prepared by the above method.
[0017] According to another aspect of the present invention, the present invention also provides an application of a fluorine-free binder as a binder in the preparation of a silicon negative electrode. In its application, silicon nanoparticles are used as active materials and Super P is used as a conductive additive. The fluorine-free binder, the active material and the conductive additive are mixed in water to form a slurry, which is then coated on a conductive foil, and then dried and cut to obtain a silicon negative electrode. The silicon negative electrode can be used in lithium-ion batteries.
[0018] The present invention uses silk fibroin as a crosslinking agent, utilizes the abundant polar groups contained in silk fibroin to interact with polyacrylic acid carboxyl groups through non-covalent hydrogen bonds, and cooperates with the in-situ conformational transformation characteristics of silk fibroin to construct a binder network structure with enhanced cohesion. The fluorine-free binder of the present invention can well maintain the structural stability of the electrode by enhancing the cohesion of the binder, thereby giving full play to the high capacity characteristics of the silicon negative electrode.
[0019] Compared with the prior art, the present invention can achieve the following beneficial effects:
[0020] 1) The preparation method of the fluorine-free binder of the present invention is simple, the materials are readily available, and it is convenient for large-scale industrial production.
[0021] 2) The fluorine-free binder of the present invention is applied to the silicon negative electrode of lithium-ion batteries to effectively enhance the adhesive properties of the binder and the problem of poor electrochemical properties and short cycle life of the silicon negative electrode caused by poor mechanical properties. The button half-cell prepared by the binder of the present invention has a good performance at 0.1C (1C = 4200mAh g -1 ) for 2 cycles and then cycled at 0.2C for 200 cycles, the specific capacity was 1900 mAh g -1 , with excellent cycle stability, while the capacity of Si / PAA prepared by traditional technology using polyacrylic acid (PAA) as silicon negative electrode binder is only maintained at 700mAh / g after 190 cycles at 0.84A / g, which shows that the improvement effect of the present invention is significant. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0023] Figure 1 Infrared spectra of untreated silk fibroin (pre-SF) and pure silk fibroin treated at different temperatures.
[0024] Figure 2 This is the infrared spectrum of silk fibroin combined with polyacrylic acid, which verifies the existence of a large number of hydrogen bond interactions between the two.
[0025] Figure 3 The peeling test of electrodes prepared with fluorine-free adhesives with different ratios of silk fibroin and polyacrylic acid;
[0026] Figure 4 This is a cycle performance diagram of a silicon negative electrode made with a fluorine-free adhesive (prepared in Example 1) that combines silk fibroin with polyacrylic acid.
[0027] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0028] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0029] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0030] Example 1
[0031] (1) 0.7 g of polyacrylic acid (PAA, Mn≈450 kDa) and 0.3 g of silk fibroin (SF, Mn≈6-10 kDa) were dissolved in 13.3 g and 9.7 g of deionized water (the resistivity of deionized water is 18.2 megohm.m), respectively.
[0032] (2) The two solutions in step (1) are mixed and stirred thoroughly to obtain a mixed colloidal solution.
[0033] (3) 0.6 g of 5% by mass ethanol solution was added dropwise to the mixed colloidal solution, and then kept in a vacuum drying oven at 140° C. for 12 h to obtain a fluorine-free adhesive with enhanced cohesion.
[0034] Example 2
[0035] (1) 0.9 g of polyacrylic acid and 0.1 g of silk fibroin were dissolved in 17.1 g and 3.23 g of deionized water (the resistivity of deionized water is 18.2 megohm.m), respectively.
[0036] (2) The two solutions in step (1) are mixed and stirred thoroughly to obtain a mixed colloidal solution.
[0037] (3) 0.45 g of ethanol solution (5%) was added dropwise to the mixed colloidal solution, and then kept in a vacuum drying oven at 140° C. for 12 h to obtain an adhesive with enhanced cohesion for characterization testing.
[0038] Example 3
[0039] (1) 0.3 g of polyacrylic acid and 0.7 g of silk fibroin were dissolved in 5.7 g and 22.63 g of deionized water (the resistivity of deionized water is 18.2 megohm.m), respectively.
[0040] (2) The two solutions in step (1) are mixed and stirred thoroughly to obtain a mixed colloidal solution.
[0041] (3) 0.85 g of ethanol solution (5%) was added dropwise to the mixed colloidal solution, and then kept in a vacuum drying oven at 140° C. for 12 h to obtain an adhesive with enhanced cohesion for characterization testing.
[0042] Comparative Example 1
[0043] As a control experiment of Example 1, a conventional adhesive was prepared. Specifically, 1 g of polyacrylic acid was dissolved in 19 g of deionized water (the resistivity of deionized water was 18.2 megaΩ·m) to prepare a fluorine-free adhesive.
[0044] Comparative Example 2
[0045] As a control experiment of Example 1, the only difference is that polyacrylic acid and silk fibroin are dissolved in deionized water at the same time to prepare a mixed colloidal solution, and the other steps and material amounts are consistent with Example 1.
[0046] In Comparative Example 2, polyacrylic acid and silk fibroin were dissolved in deionized water at the same time, resulting in agglomeration. The bonding performance of the resulting adhesive was significantly worse than that of Example 1.
[0047] The products of the above embodiments and comparative examples were tested.
[0048] The conformational transition of silk fibroin under temperature and the cross-linking of silk fibroin with polyacrylic acid were studied by infrared spectroscopy. Figure 1 As shown in the figure, from the infrared spectra of untreated silk fibroin (pre-SF) and silk fibroin treated at different temperatures, it can be seen that as the treatment temperature increases, the C=O peak increases from 1645 cm -1 (1640-1650cm -1 corresponding to disordered structure) continuously redshifts to 1625 cm -1 (1620-1640cm -1 corresponding to the β-sheet structure).
[0049] like Figure 2 As shown in the figure, after the silk fibroin was cross-linked with polyacrylic acid, the C=O peak belonging to the polyacrylic acid domain increased from 1700 cm -1 Offset to 1697cm -1 , OH peak (~3200cm -1 ) and -NH peak (~3280cm -1 ) becomes wider and flatter (e.g. Figure 2 Example 1, the weight proportion of silk fibroin is 30%). These phenomena indicate that there are a large number of hydrogen bonds between silk fibroin and polyacrylic acid. It is worth noting that when the silk fibroin content is too low (Example 2, the weight proportion of silk fibroin is 10%) or too high (Example 3, the weight proportion of silk fibroin is 70%), only the 1697 cm -1 (polyacrylic acid domain) or 1633cm -1(Silk fibroin domain) at the main C = O peak. After a large number of experiments, the optimal value range is 20-60% of the total mass of polyacrylic acid and silk fibroin, and the best effect is achieved when the silk fibroin content is 30%. Among them, when the silk fibroin content is moderate (30%), the infrared spectrum of Example 1 prepared is at 1697cm -1 (polyacrylic acid domain) and 1634cm -1 Preliminary observations show that Example 1 achieves a balance between the adhesive strength of polyacrylic acid and the cohesive strength of silk fibroin.
[0050] In order to further demonstrate the beneficial technical effects of the present invention, the fluorine-free binders of Examples 1-3 above were used as binders for silicon negative electrodes of lithium-ion batteries, and Comparative Example 1 was used as a control group. The preparation method of silicon negative electrodes is as follows:
[0051] Silicon nanoparticles were used as active materials, Super P was used as a conductive additive, and the fluorine-free binder of Examples 1-3 was used as a binder, wherein the mass ratio of active material, conductive additive, and binder was 8:1:1, and they were mixed with water as a solvent to form a uniform slurry, which was then coated on a copper foil. The electrode was then placed in a vacuum drying oven at 140°C and dried for 12 hours, and cut into small discs with a diameter of 10 mm as silicon negative electrodes.
[0052] A button-type lithium-ion battery was assembled using 1 M LiPF6 dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) containing 10% fluoroethylene carbonate (FEC) and 1% vinylene carbonate (VC) as the electrolyte, lithium sheets as symmetrical electrodes, porous polypropylene (Celgard 2500) as the separator, and CR 2032 stainless steel as the battery shell.
[0053] Since SF can undergo conformational transformation under heating conditions (disordered structure becomes β structure), the dense structure in the β structure interacts strongly with the carboxyl group in PAA through hydrogen bonds to enhance cohesion. Too little or too much SF (SF content is 10% or 70%) cannot achieve optimal adhesion strength and mechanical strength. Too little SF cannot provide better mechanical strength, and too much SF greatly reduces the adhesion strength. The right amount of SF combined with PAA can achieve optimal adhesion strength and mechanical strength. Figure 3 The peel test can prove the above point.
[0054] Cyclic performance test Figure 4 The Si / PAA electrode prepared with PAA as a binder in Comparative Example 1 exhibited a capacity of 700 mAh / g after 190 cycles at 0.84 A / g, and the electrode prepared with PAA-SF-30 in Example 1 exhibited a capacity of 700 mAh / g after 190 cycles at 0.84 A / g. -1After 190 cycles, the specific capacity is 1900 mAh / g. The cycle performance of Examples 2 and 3 is better than that of Comparative Example 1 but worse than that of Example 1, indicating that the optimal cycle performance can be achieved by optimizing the silk fibroin / polyacrylic acid ratio (the weight ratio of silk fibroin is 30%). Therefore, the present invention preferably accounts for 20-40% of the total mass of polyacrylic acid and silk fibroin, and more preferably 30%.
[0055] In order to explore the specific effect of the SF / PAA ratio on the performance, based on the preparation method of Example 1, only the SF / PAA ratio was changed to prepare the binder. Then, the electrochemical properties of electrodes prepared with binders of different ratios are listed in Table 1. By comparison, it can be seen that the importance of the SF / PAA ratio is further illustrated.
[0056] Table 1
[0057]
[0058] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a fluorine-free binder of silk fibroin cross-linked polyacrylic acid, characterized in that: The following steps are involved: S1. dissolving polyacrylic acid in deionized water to prepare a polyacrylic acid colloidal solution with a mass fraction of 3-10%; S2, dissolving silk fibroin in deionized water to prepare a silk fibroin solution with a mass fraction of 3-10%; S3, mixing the polyacrylic acid colloidal solution of step S1 and the silk fibroin solution of step S2 uniformly according to the ratio of silk fibroin to the total mass of polyacrylic acid and silk fibroin to obtain a mixed colloidal solution; S4, adding ethanol solution to the mixed colloidal solution of step S3 to transform the disordered silk fibroin into an ordered state, and then heating and drying to obtain a fluorine-free binder of silk fibroin cross-linked polyacrylic acid.
2. The method for preparing the fluorine-free binder of silk fibroin cross-linked polyacrylic acid according to claim 1, characterized in that: The resistivity of the deionized water is 18.2 MΩ.m.
3. The method for preparing the fluorine-free binder of silk fibroin cross-linked polyacrylic acid according to claim 1, characterized in that: The mass fraction of the ethanol solution is 1-5%.
4. The method for preparing the fluorine-free binder of silk fibroin cross-linked polyacrylic acid according to claim 1, characterized in that: The temperature of the heating and drying is 100-150°C.
5. The method for preparing the fluorine-free binder of silk fibroin cross-linked polyacrylic acid according to claim 1, characterized in that: In step S3, the mixture is mixed by stirring for at least 30 minutes.
6. The method for preparing the fluorine-free binder of silk fibroin cross-linked polyacrylic acid according to claim 1, characterized in that: The molecular weight (Mn) of the polyacrylic acid is 420-460 kDa, and the molecular weight (Mn) of the silk fibroin is 6-10 kDa.
7. The method for preparing the fluorine-free binder of silk fibroin cross-linked polyacrylic acid according to claim 1, characterized in that: In step S3, the silk fibroin accounts for 20-40% of the total mass of the polyacrylic acid and the silk fibroin.
8. A fluorine-free adhesive, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the fluorine-free binder according to claim 8 as a binder in preparing a silicon negative electrode.
Citation Information
Patent Citations
Thiolated polyacrylic acid water-based polymer binder for silicon-based negative electrode of lithium ion battery as well as preparation method and application of thiolated polyacrylic acid water-based polymer binder
CN116759581A
Ultra-thin hollow carbon nanospheres for sodium ion storing and manufacturing method thereof
KR1020160124964A
Self-crosslinking composite binders for electrodes
US20240079593A1
Cited By
Solid-state battery based on silicon-based negative plate and preparation method of solid-state battery
CN121905983A